(untitled) (Journal of Educational Sciences, 2016)
In order to diagnose anti vital activity of young people (mental and behavioral activity, aimed at the reduction or termination of their own social and biological functioning of) used a variant of associative test for the study of the reaction time of young people to the words-incentives relevant to the theme of death. According to the standard methods were examined 90 people aged 16 to 19 years. The results of the study showed that the average response time on a word-incentives relevant to the theme of death, more (p < 0.01)than the average response time on a neutral words, incentives, which proves the existence of the inside of a person unnatural trends, aimed against life (beginners actively operate under certain conditions). As an auxiliary method was used closest prototype of an associative test – scale suicidal intentions of the buck, which allowed to reveal that all the factors of suicidal risk (insulation, expected fatality, the final action) are found in all age groups, took part in a study. The results of this bar indicate the high intensity of suicidal intentions among young people. On the basis of indirect evaluation of the reliability of the two above methods with the help of an Integrative System of psychological testing by the method of Rorschach the peculiarities, which can be measured as indicators of anti vital activity: expressed pessimism in thinking, a state of emotional distress caused by excessive overload of negative emotions, inefficient style solutions to the problems, excessive level of reflection. In General, the obtained results allow making a conclusion about the presence of a mentally healthy young people (students in schools and universities) complex of death – affective-charged group of ideas relevant to the theme of death. The assumption, that the complex of death is related to the further factors behavior– some violence personality on you proves the need for early prevention of this syndrome. In the future, according to the results of the carried out research it is planned to certain work to develop a comprehensive strategy for the prevention of suicidal behavior, based on the development of positive thinking and the vital activity of student’s youth.